Crack development and deformation mechanisms of carbon-fiber-reinforced plastics at elevated temperatures. (March 2016) - Kubota, Yuki; Fukuda, Kohei; Hatta, Hiroshi; Langhof, Nico; Krenkel, Walter; Kogo, Yasuo
Highlights: We examined cracking mechanisms of CFRP reinforced with Kynol-based carbon fiber. Crack opening caused by the buckling of the fiber bundle expands the CFRP. The crack produced by tensile stress under pyrolysis is the trigger of the buckling. The buckling is a specific behavior of CFRP reinforced with Kynol-based carbon fiber. Abstract: Cracks that induce deformation in ablators reinforced with Kynol-based carbon fibers during pyrolysis reactions are assessed using experimental observations and theoretical estimation of tensile stress. Tensile stress in the transverse direction is produced by mismatch strain between the fiber and matrix during pyrolysis reactions and subsequently generates cracks. Observations and theoretical estimations of tensile stress using a model showed that cracking triggers buckling of fiber bundles, which consequently expands the ablator in the thickness direction. When large pores exist in the matrix, cracking relaxes the mismatch strain when tensile stress is low, thereby suppressing the buckling.